2017
DOI: 10.1093/toxsci/kfx223
|View full text |Cite
|
Sign up to set email alerts
|

From the Cover: Harmane-Induced Selective Dopaminergic Neurotoxicity in Caenorhabditis elegans

Abstract: Parkinson's disease (PD) is a debilitating neurodegenerative disease. Although numerous exposures have been linked to PD etiology, causative factors for most cases remain largely unknown. Emerging data on the neurotoxicity of heterocyclic amines suggest that this class of compounds should be examined for relevance to PD. Here, using Caenorhabditis elegans as a model system, we tested whether harmane exposure produced selective toxicity to dopamine neurons that is potentially relevant to PD. Harmane is a known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 48 publications
0
53
0
Order By: Relevance
“…Interestingly, our data using an AIA (PhIP) and a β-carboline (harmane) have suggested that transport through the dopamine transporter (DAT) was unlikely, whereas studies in non-neuronal cell lines expressing DAT suggest that 2[N]-methylated β-carboline toxicity is mediated through DAT. Thus, the uptake and toxicity mechanisms may differ between subclasses (Griggs et al , 2014; Sammi et al , 2017; Storch et al , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our data using an AIA (PhIP) and a β-carboline (harmane) have suggested that transport through the dopamine transporter (DAT) was unlikely, whereas studies in non-neuronal cell lines expressing DAT suggest that 2[N]-methylated β-carboline toxicity is mediated through DAT. Thus, the uptake and toxicity mechanisms may differ between subclasses (Griggs et al , 2014; Sammi et al , 2017; Storch et al , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…They structurally resemble the Parkinson’s disease (PD) causing substance 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and showed neurotoxic effects on dopaminergic neurons, especially as methylated forms (e.g. 2,9-dimethyl-β-carbolinium ion [2,9-dime-BC +]) (Hamann et al 2006 ; Neafsey et al 1995 ; Cruz-Hernandez et al 2018 ; Sammi et al 2018 ). Inhibition of the complex I of the respiratory chain, induction of apoptosis and activation of microglia are the main compounds of this toxic effects of 2,9-dime-BC + (Ostergren et al 2006 ; Polanski et al 2010 ; Hamann et al 2006 ; Hans et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, harman is obtained by endogenous condensation of tryptamine and pyruvate ( Figure 10 b) [ 76 , 77 , 78 ]. Harman can be generated either endogenously or exogenously through the diet (meat, roasted coffee beans, tobacco) [ 79 ], and exogenous acquisition is considered to be the main source [ 80 ]. Harman is associated with essential tremor (ET), but the mechanism is not clear [ 81 ].…”
Section: Endogenous Neurotoxinsmentioning
confidence: 99%
“…Additionally, harman and norharman reduce the DA content in PC12 cells by down-regulating the activity of TH, thus increasing cytotoxicity [ 82 ]. Using Caenorhabditis elegans as the model, it is found that harman reduces mitochondrial activity and increases ROS in dopaminergic neurons, linking it to PD [ 79 ].…”
Section: Endogenous Neurotoxinsmentioning
confidence: 99%